Thermal properties of armour steel protac 600 - Lešnjak, Matic; Kosec, Borut; Karpe, Blaž; Janjić, Goran; Gojić, Mirko; Bernetič, Jure; Kosec, Gorazd (Advanced Technologies and Materials, 2021)
Steels from the group PROTAC are distinguished by good mechanical properties and excellent armour properties even at small thicknesses. The mechanical properties of PROTAC 600 steel are known, while data on thermal properties (thermal conductivity, specific heat and temperature conductivity) are not available, so in the frame of our work we determined its thermal properties. As the first part of the work, a study and evaluation of the operation of the device for determining the thermal properties of Hot Disk TPS 2200, today one of the more modern and high-quality instruments for determining thermal properties. In the second part of the work, we performed measurements of thermal properties in accordance with the standard ISO 22007- 2 at ambient temperature. The values of thermal properties of PROTAC 600 steel at ambient temperature (approximately 22 °C) are: thermal conductivity 28.69 W/mK, specific heat 3.94 MJ/m3K, and temperature conductivity 7.29 mm2/s. We found that steel PROTAC 600 has more than 10% higher heat conductivity in comparison with the steel of previous generation PROTAC 500.